Inflammatory Responses Are Not Sufficient to Cause Delayed Neuronal Death in ATP-Induced Acute Brain Injury - Jeong, Hey-Kyeong (Public Library of Science, 2010)
BACKGROUND: Brain inflammation is accompanied by brain injury. However, it is controversial whether inflammatory responses are harmful or beneficial to neurons. Because many studies have been performed using cultured microglia and neurons, it has not been possible to assess the influence of multiple cell types and diverse factors that dynamically and continuously change in vivo. Furthermore, behavior of microglia and other inflammatory cells could have been overlooked since most studies have focused on neuronal death. Therefore, it is essential to analyze the precise roles of microglia and brain inflammation in the injured brain, and determine their contribution to neuronal damage in vivo from the onset of injury. METHODS AND FINDINGS: Acute neuronal damage was induced by stereotaxic injection of ATP into the substantia nigra pars compacta (SNpc) and the cortex of the rat brain. Inflammatory responses and their effects on neuronal damage were investigated by immunohistochemistry, electron microscopy, quantitative RT-PCR, and stereological counting, etc. ATP acutely caused death of microglia as well as neurons in a similar area within 3 h. We defined as the core region the area where both TH(+) and Iba-1(+) cells acutely died, and as the penumbra the area surrounding the core where Iba-1(+) cells showed activated morphology. In the penumbra region, morphologically activated microglia arranged around the injury sites. Monocytes filled the damaged core after neurons and microglia died. Interestingly, neither activated microglia nor monocytes expressed iNOS, a major neurotoxic inflammatory mediator. Monocytes rather expressed CD68, a marker of phagocytic activity. Importantly, the total number of dopaminergic neurons in the SNpc at 3 h (∼80% of that in the contralateral side) did not decrease further at 7 d. Similarly, in the cortex, ATP-induced neuron-damage area detected at 3 h did not increase for up to 7 d. CONCLUSIONS: Different cellular components (microglia, astrocytes, monocytes, and neutrophils) and different factors (proinflammatory and neurotrophic) could be produced in inflammatory processes depending on the nature of the injury. The results in this study suggest that the inflammatory responses of microglia and monocytes in response to ATP-induced acute injury could not be neurotoxic.